2021
DOI: 10.1097/meg.0000000000002084
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endoscopist experience, patient age and comorbidities on dose of sedation and sedation-related complications by endoscopic ultrasound

Abstract: The aim of the study is to investigate the influence of endosonographer experience and patient-related factors on the dose of sedation and sedation-related complications during endoscopic ultrasound (EUS). Methods Our retrospective analysis included EUS investigations performed between 2015 and 2018 at our institution. Sedation-related complications were defined as cardiorespiratory instability with oxygen saturation drop below 90% or prolonged low blood pressure or bradycardia. Results In total, 537 EUS exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…19 Another study revealed that trainee involvement during EUS could be associated with an increased risk of adverse events, particularly in the first 3 months of the training. The overall adverse event incidence was reported to be 3.4%, 20 slightly higher than in the previous literature (1% to 3%) 8,21 and compared to results presented here (2.1%). In this context, the amount of training may be more appropriate than the duration alone to evaluate adverse events.…”
Section: Discussioncontrasting
confidence: 66%
“…19 Another study revealed that trainee involvement during EUS could be associated with an increased risk of adverse events, particularly in the first 3 months of the training. The overall adverse event incidence was reported to be 3.4%, 20 slightly higher than in the previous literature (1% to 3%) 8,21 and compared to results presented here (2.1%). In this context, the amount of training may be more appropriate than the duration alone to evaluate adverse events.…”
Section: Discussioncontrasting
confidence: 66%
“…One important concern regarding sedation for endoscopy is sedation-related complications [ 15 ], which can lead to significant morbidity and occasional mortality in patients [ 16 ]. In particular, propofol is often responsible for producing serious cardiovascular and respiratory depression, often requiring endotracheal intubation [ 17 ], but few studies have reported similar effects of remimazolam.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, sedation for endoscopy may cause severe morbidity, 3 especially respiratory depression. 4 Therefore, airway management is important.…”
Section: Introductionmentioning
confidence: 99%